Potensi Snack Bar Berbasis Blondo dan Substitusi Tepung Anggur Laut untuk Mendukung Performa Atlet: The Potential of Blondo-Based Snack Bars and Sea Grape Flour Substitution to Support Athlete Performance - Devi, Shalma; Aeni, Malin Nur; Insyirah, Thifal Hazimah Al; Azmi, Haikal Rizky; Gunawan, Antonius; Nasrullah, Nanang (Universitas Airlangga, 2025)
Background: Sports injuries represented an unavoidable morbidity condition among athletes. Data from the 2016 Summer Olympics in Rio de Janeiro demonstrated that 1,101 out of 11,274 athletes (9.8%) experienced injuries, with 19% sustaining two or more types of injuries. In world championships, 81 injury cases per 1,000 athletes were recorded. Muscle injuries dominated 30-40% of cases in soccer players and more than 59% in weightlifters. Blondo, a coconut oil industry by-product, contained 16.9 g protein, 23.9 g fat, 31.8 g carbohydrates, and 341 kcal energy per 100 g. Sea grapes (Caulerpa Lentillifera) contained chlorophyll a and b, which functioned as antioxidants to protect body cells from post-exercise free radicals. Objectives: This study aimed to analyze the chemical and sensory characteristics of blondo and sea grape-based snack bars. Methods: The research employed a Completely Randomized Design with three formulas (F1: 50%, F2: 75%, F3: 100% blondo). Analysis included proximate testing, fiber content, antioxidant activity, and organoleptic testing. Results: ANOVA analysis revealed that blondo addition did not significantly affect the measured variables (p-value>0.05). However, moisture, ash, protein, fat, and fiber content increased, while carbohydrate content decreased, potentially benefiting athletes. Additionally, decreased IC50 values indicated increased antioxidant activity with blondo addition. Conclusions: Blondo and sea grapes demonstrated potential as sports food ingredients, with F3 being the most preferred formula, containing 518.5 kcal, 14.11 g protein, 27.17 g fat, and 54.27 g carbohydrates.